A CORTE CONSTITUCIONAL MONOCRÁTICA: QUESTÕES SOBRE AS DECISÕES MONOCRÁTICAS EM CONTROLE DE CONSTITUCIONALIDADE CONCENTRADO: (Reflection and Critique Law Magazine, 2024)
It is easy to see that the number of cases judged by the Federal Supreme Court has been increasing, especially in recent decades, reaching extraordinary numbers, and imposing obstacles for the Court to fulfill its main role, which is the analysis and control of constitutionality. This is due to several factors, among them the exceptionally broad powers of the Federal Supreme Court; the constitutionality control system adopted by Brazil, which encompasses both the concentrated and the diffuse model; the extension of the Constitution, which corroborates with the indirect increase of the competences of the Constitutional Court, among others. In order to provide efficiency to the judgments, the possibility of issuing monocratic decisions was created, but its legitimacy and respect for the separation of powers are questioned, especially when in actions of concentrated constitutionality control, since by preliminary decision, of a single Minister, the effect of the Law, processed by the Legislative and sanctioned by the Executive, is suspended. Therefore, through the hypothetical-deductive method, with the use of bibliographic research and data, it is concluded that it represents an imbalance between powers and negatively affects democratic mechanisms.